Successful Endoscopic Closure of Esophageal Perforation in Boerhaave Syndrome Using the Over-the-Scope Clip - Estorninho,João (2023)
Abstract Boerhaave syndrome (BS) is a rare but potentially fatal condition. Although surgery is considered the standard treatment, endoscopic therapy has acquired an important role as a minimally invasive management approach. The authors describe 2 cases of middle-aged male patients, presenting with spontaneous esophageal perforation after severe straining and vomiting. In the first case, the patient presented with a bone impaction in the upper esophagus successfully removed by rigid esophagoscopy. After the procedure, a chest X-ray/cervicothoracic computerized tomography scan (CT) showed a left hydropneumothorax and pneumomediastinum with oral contrast leak at the lower esophagus. In the second case, the patient presented to the Emergency Department with severe chest pain after an episode of vomiting. The CT showed a massive pneumomediastinum, subcutaneous emphysema, and an oral contrast leak compatible with BS. The patient was initially submitted to surgical suture, but contrast extravasation persisted after 12 days. After multidisciplinary team discussion of both patients, an upper gastrointestinal endoscopy was performed, which revealed pericentimetric wall defects at the distal esophagus. These were successfully closed using an over-the-scope clip (OTSC). After at least a 9-month follow-up, patients have remained clinically well with no relapse. The authors highlight the severity of these clinical cases and the endoscopic option that proved to be decisive in addressing BS. The favorable outcomes suggest a role for the OTSC approach in closing spontaneous esophageal perforation both as first-line and as rescue therapy after a surgical failure.